(Salen)Titanium‐Catalyzed Asymmetric Hydrogen Atom Transfer for Epoxides Reduction. Issue 50 (15th November 2022) - Xu, Zhongyun; Shen, Jian; Li, Longfei; Chen, Wanjiao; Li, Shengxiao; Jiang, Jie; Zhang, Yong‐Qiang
Abstract: Asymmetric hydrogen atom transfer (HAT) represents arguably one of the most straightforward access to the significant chiral tertiary carbon centers, however, remains a long‐standing challenge. Herein, the first example of catalytic coordination‐induced asymmetric HAT reaction has been developed relying on a sequential (salen)Ti III ‐initiated radical generation and (salen)Ti IV ‐controlled enantioselective HAT process. The reaction transforms easily accessible glycidic esters, thioesters and amides to synthetically valuable formal formaldehyde aldol adducts in an enantioconvergent manner, along with broad scope and highly regio‐ and enantioselectivities. Abstract : A catalytic and asymmetric hydrogen atom transfer (HAT) reaction is achieved through a sequential (salen)Ti III ‐initiated radical generation and (salen)Ti IV ‐induced enantioselective HAT process. It enables an enantioconvergent approach from readily accessible racemic glycidic esters and amides to synthetically valuable enantioenriched formal formaldehyde aldol products with high regio‐ and enantioselectivity.